Influence of early extubation on post‐operative outcomes after pediatric lung transplantation. (11th August 2020) - Labarinas, Sonia; Coss‐Bu, Jorge A.; Onyearugbulem, Chinyere; Heinle, Jeffery S; Mallory, George B; Gazzaneo, Maria C.
Abstract: Lung transplantation has become an accepted therapeutic option for a select group of children with end‐stage lung disease. We evaluated the impact of early extubation in a pediatric lung transplant population and its post‐operative outcomes. Single‐center retrospective study. PICU within a tertiary academic pediatric hospital. Patients <22 years after pulmonary transplant between January 2011 and December 2016. A total of 74 patients underwent lung transplantation. The primary pretransplantation diagnoses included cystic fibrosis (58%), pulmonary fibrosis (9%), and surfactant dysfunction disorders (10%). Of 60 patients, 36 (60%) were extubated within 24 hours and 24 patients after 24 hours (40%). A total of seven patients (11.6%) required reintubation within 24 hours. Median length of stay for the early extubation group was shorter at 3 days ([(IQR) 2.2‐4.7]) compared to 5 days (IQR, 3‐7) ( P  = .02) in the late extubation group. Median costs were lower for the early extubation group with 13, 833 US dollars (IQR, 9980‐22, 822) vs 23 671 US dollars (IQR, 16 673‐39 267) ( P  = .043). Fourteen patients were in the PICU prior to their transplantation; this did not affect their early extubation success. Neither did the fact of requiring invasive or non‐invasive mechanical ventilation before transplantation. Early extubation appears to be safe in a pediatric population after lung transplantation and is associated with a shorter LOS and decreased hospital costs. It may prevent known complications associated with mechanical ventilation.